Cadaveric Study Evaluating the Potential for Hindfoot Endoscopy and Flexor Hallucis Longus Tendoscopy Using a 1.9-mm Diameter Needle Arthroscope - Yoshiharu Shimozono MD, PhD; Ryuzo Arai MD, PhD; Yutaka Kuroda MD, PhD; Hiromu Ito MD, PhD; Shuichi Matsuda MD, PhD (Foot & Ankle Orthopaedics)
Background: Hindfoot endoscopy is an effective treatment for posterior ankle impingement syndrome (PAIS) and flexor hallucis longus (FHL) tendon disorders. However, FHL tendoscopy, especially from the posteromedial portal, carries a risk of tibial nerve damage. A needle-arthroscopic system with a 1.9-mm-diameter arthroscope, a semirigid frame, and a 0-degree direction of view has been introduced. This study aimed to evaluate the efficacy and safety of this system in visualizing and reaching significant structures in hindfoot endoscopy and FHL tendoscopy through the posteromedial and posterolateral portals using a cadaveric model. Methods: The 1.9-mm-diameter arthroscopic system (NanoScope, Arthrex) was used to perform hindfoot endoscopy in 6 human donor ankles (3 pairs). The arthroscope tube is 9.5 cm long, semirigid, and has an outer diameter of 1.9 mm, a 0-degree direction of view, and a 120-degree field of view. Posteromedial and posterolateral portals were established. Visualization and operative reach were recorded, including the posterolateral talar process, posterior talofibular ligament, intermalleolar ligament, subtalar joint, and FHL tendon. The neurovascular bundle and FHL tendon were examined for kinks or damage. Results: All significant structures were successfully visualized in all specimens. The wide 120-degree field of view facilitated adequate visualization of all structures. In all specimens, the FHL tendon was visualized from the ankle joint to the knot of Henry (zones 1 and 2), and the flexor digitorum longus tendon was observed via both portals. There were no signs of neurovascular damage from either the posterolateral or posteromedial portals. Conclusion: In this cadaver experiment without known pathology, use of a 1.9-mm-diameter needle-arthroscopy with a 0-degree direction of view provided effective visualization of all significant structures in treating PAIS and FHL tendon disorders. It appears that FHL tendoscopy can be performed from the level of the ankle joint to the knot of Henry via both the posterolateral and posteromedial portals.